Pelatihan Pembuatan Buket Bunga dan Snack bagi Remaja Putri dan Ibu Rumah Tangga di Kelurahan Pulokerto, Palembang - Siti Rohima; Anna Yulianita; Sabam Syahputra Manurung; Puspa Utami (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2026)
Low household income and limited technical skills represent the primary challenges faced by the community in Talang Ubi, Pulokerto Village, Palembang, which hinder the development of creative economy potential based on local wisdom. This community service activity aims to improve the knowledge and skills of housewives and young women through flower and snack bouquet production training as a strategic effort to enhance their quality of life. The implementation method employed was Participatory Action Research (PAR), encompassing the stages of problem diagnosis, solution planning, action (through lectures, interactive discussions, and hands-on training), and reflection. Evaluation was conducted comprehensively using pre-test and post-test instruments among 20 selected participants. The results indicated a significant increase in participant competence, with a 100% success rate. Evaluation data recorded an implementation achievement of 91%, material mastery of 94%, and target material achievement of 90%. In conclusion, the application of the PAR method in this training proved effective in economically empowering women and is aligned with the achievement of SDG 1 (No Poverty), SDG 4 (Quality Education), and SDG 8 (Decent Work and Economic Growth). This activity provides a tangible contribution to strengthening the local creative economy ecosystem sustainably and supports the achievement of Universitas Sriwijaya's Key Performance Indicators (IKU).